Positive allosteric modulation of the human metabotropic glutamate receptor 4 (hmGluR4) by SIB-1893 and MPEP - Mathiesen, Jesper Mosolff (2003)
We have identified 2-methyl-6-(2-phenylethenyl)pyridine (SIB-1893) and 2-methyl-6-phenylethynyl pyridine hydrochloride (MPEP) as positive allosteric modulators for the hmGluR4. SIB-1893 and MPEP enhanced the potency and efficacy of L-2-amino-4-phophonobutyrate (L-AP4) in guanosine 5′-O-(3-[(35)S]thiotriphosphate ([(35)S]GTPγS) binding and efficacy in cAMP studies. These effects were fully blocked by the mGluR4 competitive antagonist (RS)-α-cyclopropyl-4-phosphonophenylglycine (CPPG), indicating a dependency on receptor activation. Although SIB-1893 and MPEP had no effects alone in GTPγS binding, effects were observed in the cell-based cAMP assay due to media-derived activation as indicated by CPPG inhibition. Positive modulation of the mGluR4 was a receptor-specific effect since SIB-1893 and MPEP had neither effects on mGluR2-expressing cells nor on the parent BHK cell line. In [(3)H]L-AP4 binding, a two-fold decrease in K(D) but not in B(max) was observed with 100 μM SIB-1893, whereas MPEP affected neither parameter. Finally, SIB-1893 and MPEP failed to displace [(3)H]L-AP4 binding. Taken together, these data identify positive allosteric modulators for the hmGluR4.